Main Factors that Explain Organic Food Purchase Intention: A Systematic Review - Leyva-Hernández, Sandra Nelly; González-Rosales, Virginia Margarita; Galván Mendoza, Oscar; Toledo-López, Arcelia (My University, 2022)
This study sought to understand the factors behind the intention towards buying organic products mentioned in the existing literature and provide conceptual and theoretical guidelines for future research on the subject. A systematic revision of original research papers included in Scopus and Web of Science databases during the period 2011-2021 was conducted, resulting in a sample of 162 articles. The results show that the attitude, values, and confidence of the consumer were the main factors in the intention to buy organic foods. Moreover, it was found that the theory of planned behavior was the most used theoretical framework in the analysis of organic foods purchasing. The changes brought by the covid-19 pandemic are manifested in consumers’ values and their implications to the sale of this type of foods. We propose to consider consumers’ values as variables that intertwine the rational and motivational approaches to consumption analysis. It is also proposed to understand the purchase intention underlying the stimulation of attitudes and the confidence of consumers due to their values. Finally, it is suggested to consider the analysis of the mediating effect of attitudes and trust in the relationship between values and purchase intention.

Esta investigación tuvo como objetivo comprender los factores tras la intención de compra de productos orgánicos mencionados en la literatura y proporcionar pautas conceptuales y teóricas para futuras investigaciones sobre el tema. Para ello, se realizó una revisión sistemática de artículos de investigación originales incluidos en las bases de datos Scopus y Web of Science durante el período 2011-2021, que arrojó una muestra de 162 artículos. Los resultados muestran que la actitud, los valores y la confianza del consumidor son los principales factores asociados a la intención de compra de alimentos orgánicos. Además, se identificó que la teoría del comportamiento planificado es el marco teórico más empleado para el análisis de la intención de compra de este tipo de alimentos. Los cambios generados por la pandemia de covid-19 se manifiestan en los valores de los consumidores y sus implicaciones para la venta de alimentos orgánicos. En consecuencia, se sugiere considerar los valores de los consumidores como variables que entrelazan los enfoques racional y motivacional en el análisis de los patrones de consumo. Además, se recomienda estudiar la intención de compra que subyace a la estimulación de las actitudes y la confianza de los consumidores con base en sus valores. Finalmente, se propone incorporar el análisis del efecto mediador de las actitudes y la confianza en la relación entre los valores y la intención de compra.